140m+60n-160m-50n=

Simple and best practice solution for 140m+60n-160m-50n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 140m+60n-160m-50n= equation:


Simplifying
140m + 60n + -160m + -50n = 0

Reorder the terms:
140m + -160m + 60n + -50n = 0

Combine like terms: 140m + -160m = -20m
-20m + 60n + -50n = 0

Combine like terms: 60n + -50n = 10n
-20m + 10n = 0

Solving
-20m + 10n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-10n' to each side of the equation.
-20m + 10n + -10n = 0 + -10n

Combine like terms: 10n + -10n = 0
-20m + 0 = 0 + -10n
-20m = 0 + -10n
Remove the zero:
-20m = -10n

Divide each side by '-20'.
m = 0.5n

Simplifying
m = 0.5n

See similar equations:

| [5n+12]+2=0 | | 2(c-5)=8c+2 | | 7u+7q-8= | | 6=(y+2) | | 8(-5-n)=-22+n | | 19x+24x+17x=180 | | 12-4b=4 | | 2(x+1)=7+2x | | 19x+24x=180 | | 4c-5d+2c-6d= | | -85=7x-8 | | 4(y+8)=0.5(4y-8) | | y+2x=40 | | 4x^3/3xy^-4 | | 0=16-3x-4y | | 13x+9=3x+9 | | -51=-2(1-5n)-(1-6m) | | x(6x-7)=o | | 5r^2-46r+48=0 | | 2q+3=11 | | 4a+2b+c=1000 | | 2x+8=2(1+2x) | | 5n^2+38n-63=0 | | -7c+4-c=-2(c+3) | | -2x(x+5)=3x-15 | | 0x+8=20 | | 4x-10=-4x | | N^2/2n-1 | | 3(3x+4)=3x+18 | | 10a=3.5(17) | | 2x+58=3(2+5x) | | 8x-(4x+7)+11=2x |

Equations solver categories